1999
DOI: 10.1016/s0014-5793(99)00291-4
|View full text |Cite
|
Sign up to set email alerts
|

The hypothalamic satiety peptide CART is expressed in anorectic and non‐anorectic pancreatic islet tumors and in the normal islet of Langerhans

Abstract: The hypothalamic satiety peptide CART (cocaine and amphetamine regulated transcript) is expressed at high levels in anorectic rat glucagonomas but not in hypoglycemic insulinomas. However, a non-anorectic metastasis derived from the glucagonoma retained high CART expression levels and produced circulating CART levels comparable to that of the anorectic tumors. Moreover, distinct glucagonoma lines derived by stable HES-1 transfection of the insulinoma caused severe anorexia but retained low circulating levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 29 publications
2
64
0
3
Order By: Relevance
“…Nara-ashizawa et al demonstrated that CRH mRNA in the PVN was up-regulated in cachectic tumor-bearing mice [41]. Jensen et al demonstrated that hypothalamic CART is highly expressed in anorectic rat glucagonoma [48].…”
Section: Orexigenic Neuropeptides (Npy Agrp Orexins Mch) In Anorexmentioning
confidence: 99%
“…Nara-ashizawa et al demonstrated that CRH mRNA in the PVN was up-regulated in cachectic tumor-bearing mice [41]. Jensen et al demonstrated that hypothalamic CART is highly expressed in anorectic rat glucagonoma [48].…”
Section: Orexigenic Neuropeptides (Npy Agrp Orexins Mch) In Anorexmentioning
confidence: 99%
“…Previous studies revealed the presence of CART both in the central and peripheral nervous system, including primary sensory neurons (Dun et al 2000), cholinergic nerves of pancreatic islets (Jensen et al 1999), intramural ganglia of the urinary bladder trigone (Zacharko-Siembida and Arciszewski 2014a) and neurons supplying the adrenal and thyroid glands .…”
Section: Introductionmentioning
confidence: 99%
“…2). In the normal state, CART is expressed in rats in a subpopulation of delta-and beta cells [7,21,24,25]. In mice, it is also found in a subpopulation of beta cells but it is barely detected in delta cells.…”
Section: Cart and Pancreatic Isletsmentioning
confidence: 99%
“…Low [7,21,24,25] Low [7,18,21] + [7] Undetected [21,24] Undetected [7,18,21] + [7] + [7,21,24,25] Low/Undetected [18,21] - †…”
Section: Ratmentioning
confidence: 99%